Digital Versus Printed Publication: Results From an Agricultural Extension Readership Survey - Jacob E. McCarthy; David K. Beede; Annie Edgecomb (Journal of Applied Communications, 2008)
While research demonstrates that most agricultural producers prefer to receive research and other educational information in printed forms, such as newsletters and magazines, acceptance of the Internet is increasing.
Keywords: Digital Versus Printed Publication; Agricultural Extension